Ecophysiology and Development Opportunities of Durian (Durio zibethinus) Through Agroforestry Systems in the Southern Slopes of Mount Merapi, Indonesia - Febri Arif Cahyo Wibowo; Priyono Suryanto; Eny Faridah (Jurnal Ilmu Kehutanan)
Durian (Durio zibethinus) is widely cultivated through agroforestry system in the Cangkringan and Kemalang sub district, in the southern slope of Merapi Mountain, Yogyakarta, Indonesia. Although the area to crop Durian has increased since 1990’s, the productions were not optimal, which probably is due to lack of silviculture treatments. This research aimed to assess the influence of physiological and environmental factors on Durian planted through agroforestry system of homegarden and dryland, and to analyze the condition of durian root systems under those two locations. Ecophysiological studies of Durian were carried out by leaf sampling for physiological properties (i.e.nitrate reductase activity, relative water content, stomata, proline and chlorophyll content) and field observations on environmental factors (i.e. mean air temperature, wind speed, light and moisture). Variance analysis was conducted with advanced DMRT and stepwise statistical analysis. Observation on durian rooting system was conducted by geoelectric resistivity method. The results showed that the soil conditions of the two locations were relatively similar and the root rhizosphere of durian mostly consisted of small stones, sand, and water. It was found that the Durian fruit yield between agroforestry system of homegarden and dryland were different, and based on the stepwise statistical analysis, the Durian production was mostly influenced by wind speed. It was observed that the presence of wind has caused the abscission of young fruits, where faster wind resulted in more abscission of young fruits. Another factor affecting the Durian production was rainfall. It was observed that rainfall has interfered the metabolism processes of the fruits causing fruits being rotten before harvest time.